2012
DOI: 10.4253/wjge.v4.i7.323
|View full text |Cite
|
Sign up to set email alerts
|

A study of the changes in the cause of peptic ulcer bleeding

Abstract: It's found that the primary cause of peptic ulcer bleeding changed from H. pylori infection to use of NSAIDs over the 7-year period of study. It seems that the number of low-dose aspirin users has increased with the increase in the proportion of vascular disease. It is necessary to take measures to prevent peptic ulcer bleeding among NSAIDs and low dose aspirin users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…In last decade, usage of non-steroidal anti-inflamatory drugs (NSAID) also increased, especially in the increasing elderly population (16,17). The use of NSAIDs is associated with an increased risk of bleeding ulcers (18,19). In Turkey, life expectancy is also increasing by time.…”
Section: Original Articlementioning
confidence: 99%
“…In last decade, usage of non-steroidal anti-inflamatory drugs (NSAID) also increased, especially in the increasing elderly population (16,17). The use of NSAIDs is associated with an increased risk of bleeding ulcers (18,19). In Turkey, life expectancy is also increasing by time.…”
Section: Original Articlementioning
confidence: 99%
“…It has been demonstrated that Helicobacter pylori infection and the use of nonsteroidal anti-inflammatory drugs (NSAIDs) are the main causes of peptic ulcers [1,2]. In a study from Spain in 2004, H. pylori infection was recognized in 87% of patients with gastric ulcers and 96% of patients with duodenal ulcers [3].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the incidence of peptic ulcer has also decreased both in Western countries [5,6] and in Japan [4]. By contrast, the use of NSAIDs and antithrombotic agents has recently been rising because of the increase in the elderly population [1]. The use of NSAIDs is associated with an increased risk of major upper gastrointestinal complications, including bleeding and perforation [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations